Photo-Grafting Copolymerization of PP Nonwoven Fabric and Its Application for Acidic Dye Adsorption and Filtration - 石小丽 刘颖 宋欢 万恒 朱新生 潘志娟 (东华大学学报（英文版）, 2014)
The monomer methacrylamido propyl trimethy ammonium chloride（ MAPTAC） was copolymerized onto the fiber surface of polypropylene（ PP） nonwoven fabric under ultroviole radiation. The weak acid red GN dye adsorption and adsorptive filtration performance of the resulted PP fabrics were investigated.The results showed that the grafting copolymerization preferred to happen in the inner layer of the fabrics. The water flux of the grafted fabrics decreases with the increase of grafting yield. The collapse of the grafted polymer chains causes the flux increase in acidic condition,or vice versa at alkaline version. The coiling of the polyelectrolyte chains upon the dye adsorption seems to violate the routine assumption of the rigid substrate, and this gets the adsorption energy constant negative. The static adsorption process follows the Lagergren＇s pseudo-second order kinetic equation. The removals of circa（ ca.） 100% of the total permeation volume3 500 mL simulated dye wastewater was reached during permeation.The dye adsorbed fabrics were regenerated by the mixed media of the cationic surfactant / ethanol /water. The grafted fabric assumes stable fabric integrity and stability during permeation,and presents excellent dye adsorption capacity,easy desorption, and repeatable utilization.